Skin melanoma imaging using ultrasonography: a literature review - Piłat, Paweł; Borzęcki, Adam; Jazienicki, Mieczysław; Krasowska, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Melanoma is one of the most unpredictable tumours, as regards both morphology and the course of disease. It may have different clinical forms making it very difficult to diagnose. Therefore, it often surprises even the most experienced dermatologists. Despite numerous attempts, no efficient treatment of advanced stages have been elaborated, and early detection and removal of a skin lesion currently constitutes the most efficient treatment method. Diagnostics uses different types of dermoscopic techniques characterised by considerable sensitivity and specificity in detecting melanoma at an early developmental stage. A continuous development of medical technologies leads to improving many methods of skin lesion imaging. Ultrasonography is one of these methods, enabling evaluation of the thickness of melanoma in vivo with high precision. Change thickness is the decisive factor influencing 5-year survival. The paper evaluates the usefulness of high-frequency ultrasonography (HFUS) in pre-operative melanoma imaging on the basis of literature review. Additionally, the use, role and placement of HFUS in skin melanoma diagnostics is determined.